Determination of the effectiveness of the application of radial wheel pair installation and body tilt on high-speed vehicles when driving on curved sections of the track - Masliev, Vyacheslav; Yakunin, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is a high-speed railroad vehicle. The introduction of high-speed traffic on Ukrzaliznytsia is constrained by the structure of the track, which has up to 30% of curved sections where the speed is limited in terms of traffic safety and passenger comfort. In addition, with increasing speed, the wear of wheel rims increases significantly. This gives rise to the problem of organizing high-speed traffic. One direction to solve it (very expensive) is to design a high-speed track where curved sections are absent or have a radius of several kilometers. Another option (less expensive) is to design vehicles with devices that partially compensate for centrifugal force – gravitational, by tilting the body. To reduce the wear of wheel rims, systems for radial installation of wheelsets in curves are quite effective. Almost 50 years of experience in using radial wheelset and body tilt systems on curved track sections in Switzerland, Norway, etc. proves their high efficiency in solving the problems of rim wear and passenger comfort. The study reported here was conducted by computer simulation. For this purpose, a mathematical model of the dynamics of high-speed rail vehicle movement along a curved track section with a radius of 350 m and an increase in the outer rail by 0.15 m was synthesized. The feasibility of simultaneously equipping vehicles with systems for forced radial wheelsets and forced body tilt has been proven. On routes containing 30% of curves with a radius close to 350 m, this will reduce train travel time by 8.3%. This percentage will increase proportionally in accordance with the increase in the length of curved sections along the route